The last song [videorecording (DVD)] - Robinson, Julie Anne; Cyrus, Miley, 1992-; Hemsworth, Liam, 1990-; Coleman, Bobby, 1997-; Sparks, Nicholas (Touchstone Home Entertainment : Distributed by Buena Vista Home Entertainment, 2010)
Seventeen, angry, and alienated from her estranged father, Veronica 'Ronnie' Miller's life gets turned inside out when her mother forces her to spend the summer with him in the small Georgia beach town where he lives. Here, Ronnie finds salvation, friendship, second chances, and first love.